Halal Cosmetics Products Used in Islamic Boarding School Analysis of the Halal Product Standard of Fatwa (MUI) - Setiawan bin Lahuri; Muhammad Rizal Pranoto (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Purpose: This study aims to present perfume used as a product in halal standardization. Halal standards in products are currently in legal interest to ensure the quality and trustworthiness of products that are widely circulating in the market. The application of halal standardization must be considered by all consumers, especially by students and teachers as people who know and learn about Islamic teaching. Like in the phenomenon of previous research found the humans are using perfume only to preserve appearances without any attention for the essential elements of the product.Design/Method/Approach: The approach in this research is to use descriptive qualitative methods. In connection with this, data collection was also carried out regarding the number of students and teachers, the number and type of perfume, as well as sales data and applicable halal product standards. The research data was obtained from the interview of the students and the teachers of Darussalam Gontor Islamic Institution in Magelang.Findings: The results of this study found some of the students and teachers at the Darussalam Gontor Modern Islamic Institution Magelang are using the perfume as cosmetics daily use. The sales data and the applicable halal product standards concluded that perfume products sold by the operation section and mini market and used by most of the students and teacher, have not all had halal standards and certificates. In addition, both students and teachers still do not know about the halal standards that apply to perfume products.Originality/Values: It can be concluded that the research perfume products sold by the student and teachers have not all had halal standards and certificates. However, MUI still urges the public to choose cosmetics that are halal and avoid cosmetic products that are unclean or haram.